P-Median Model for Locating Emergency Flood Shelters - Wichitsawat Suksawat Na Ayuhdya (My University, 2023)
Nong Khai and Udon Thani provinces since these two provinces are on the south bank opposite Vientiane. However, Floods during the monsoon season caused problems, and the drainage infrastructure project is not complete. Therefore, the authority must prepare a response, mitigation, and recovery plan. So, the key element of this plan is to find suitable locations for emergency flood shelters while reducing transportation costs. In this paper, the scenario-based facility location model was used to locate emergency flood shelters. Historical data for detour routes and population size were also incorporated. Two scenarios were run. The optimization model was tested against data from the years 2017, 2018, and 2019. Numerical results show that Mueang Udon Thani and 3-Nong Han are the key districts for emergency flood shelters.
Keywords: Facility Location and Emergency Management; Evacuation and Crowd Dynamics; Vehicle Routing Optimization Methods